A CORRELATION BETWEEN SELF-CONFIDENCE AND THE STUDENTSâ SPEAKING SKILL - Roysmanto, Roysmanto (Research And Innovation In Language Learning (RILL), 2018)
This research entitled âA Correlation between Self-Confidence and the Studentsâ Speaking Skillâ. The objective of the research was to investigate whether there is a significance correlation or not between self-confidence and the studentsâ speaking skill of the third grade of Swadaya Gunung Jati University in academic year 2014/2015, the writer obtained the data by the quantitative research. The writer used correlational design. The population was the third grade students of Swadaya Gunung Jati University Cirebon. There were 40 students as sample. The data were collected through interview and questionnaire. The results of this research shows that there is a significance correlation between score of questionnaire and interview. It was representedÂ  in the test hypothesis that tobserved is higher than ttable (10.39 > 0.320). So the writer concluded that there is a significance correlation between self-confidence and the studentsâ speaking skill.Â Keywords: Correlation, Self-confidence, Speaking skill